Phytochemical properties and in-vitro cytotoxicity, genotoxicity and mutagenicity assessment of ethanolic and aqueous extracts of Argyrolobium roseum (Camb.) - Naeem Rasool; Muhammad Ovais Omer; Aqeel Javeed; Muhammad Nawaz; Muhammad Adil Rasheed; Muhammad Imran; Muzzamal Hussain; Amal Fahmy Dawood; Zarina Mushtaq; Entessar Al Jbawi (International Journal of Food Properties, 2023)
The current study aimed to investigate the phenolic and flavonoid contents, cytotoxicity, genotoxicity, and mutagenicity of ethanolic and aqueous extracts of A. roseum (Camb.). The MTT assay was used to determine cytotoxicity, Comet assay was used to determine genotoxicity and mutagenicity of extracts was assessed through Ames test. The results showed that total phenolic contents were higher in aqueous extract (538.26 mg GAE/100 g); however, total flavonoid contents were significantly higher in ethanolic extract (6553.29 mg Eq. of Quercetin/100 g). The cells survival percentage was significantly (P <.05) decreased as concentrations of ethanolic extract increased. However, no significant toxicity was observed in groups treated with 0.031–0.25 mg/ml of ethanolic extract of A. roseum compared to negative control (P > .05). IC50 of ethanolic and aqueous extract of A. roseum was 5.54 mg/ml and 11.39 mg/ml, respectively. The results indicated that all concentration groups of ethanolic and aqueous extract of A. roseum significantly (P < .05) lowered DNA damage than positive control group. The lowest DNA damage was observed at 0.031 and 0.062 mg/ml in both aqueous and ethanolic extracts. Moreover, at higher concentrations of 4, 8, and 16 mg/ml of both ethanolic and aqueous extract observed 100% DNA damage cells (comet cells). Moreover, Ames mutagenicity showed that no significant (P > .05) changes were observed in revertant colonies of both bacterial strains (T 98; T 100) at 0.25, 0.5, and 1 mg/ml concentrations of both aqueous and ethanolic extract of A. roseum as MI index was less than 2. The research concluded that A. roseum extracts exhibited no cytotoxicity, genotoxicity, and mutagenicity at lower concentrations (≤2 mg/ml).